Application Prospect of Coal-fired coupled Biomass in Technical Transformation of Thermal Power Unit. Issue 2 (February 2020) - Chen, Xiufang; Yan, Hanbing; Guo, Liqiang; Liu, Fengchun
Abstract: The development of thermal power units in China is restricted. In the process of transformation, coupled biomass power generation is the main direction of the transformation in the fuel sides. This paper introduces the constraints of thermal power units, the main ways of coal-fired coupling power generation, the technical route of coupling biomass in all of 84 pilot thermal power units and the problems faced by coupled biomass power generation. On this basis, some suggestions on the application of coal-fired coupling power generation in enterprises are put forward.